Thomas & friends, all engines go. Off the rails! [videorecording (DVD)] - Allcroft, Britt; Suvalle, Rick, 1972- (NCircle Entertainment, 2023)
Thomas the Tank Engine is back! Deliveries will go awry, new areas of the island will be explored, and animals will end up in places they shouldn't be while Thomas and his friends grow from these surprises. Ashima returns from the Nilgiri Mountain Railway! Whiff tinkers in his Recycling Plant. Even Salty the Diesel Engine returns singing shanties from across the seas. The loc-amigos say "all aboard" to these familiar friends and debut character Bruno, the brake car. With brand new songs and bigger, better adventures, this season is bound to be a toot-ally awesome journey! Purposeful, playful stories, age-appropriate themes brought to life in a comedic and playful way have always been at the heart of Thomas's content. The series will continue to deliver meaningful life lessons. For Thomas, the "high road" is not always the easy choice, but it is making that choice that positions him as a role model for young viewers.